From Theatre Research in Bali To directing Bali dream at Butler University, USA (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article examines the role and trajectory of the art director from initiating theatre research in Bali to directing Bali Dream, a main stage theatre production that utilized puppets, masks, choir, and animated objects. The show premiered in November 2012 at Butler University, Indianapolis, USA. Sharing detailed experiences of the director, this article offers an account of the creative process undertaken in realizing Bali Dream. This development trajectory includes early development in the local Balinese village, then at the Indonesian Art Institute in Bali (ISI Denpasar), and at the campus of Butler University with the American student actors and actresses. Ultimately, this article shares how the role of director can prepare for a show like Bali Dream, as well as and the creative responses required to face the shifting challenges and experiences working with college students and village children from East to West.Keywords: Theatre East-West. Theatrical staging. Creation process. Bali Dream.